2012
DOI: 10.5761/atcs.oa.11.01811
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Status of Mediastinal Lymph Nodes after Preoperative Concurrent Chemoradiotherapy Determines Prognosis in Patients with Non-Small Cell Lung Cancer

Abstract: Objectives: The benefits of preoperative chemoradiotherapy for advanced nonsmall cell lung cancer (NSCLC) remain controversial. To evaluate prognostic indicators of clinical N2 NSCLC patients treated with concurrent chemotherapy followed by pulmonary resection, we performed a retrospective study. Methods: We retrospectively investigated 52 patients with pathologically proven N2 NSCLC who underwent concurrent chemoradiotherapy before pulmonary resection. Each received 2 cycles of cisplatin-vinca alkaloid-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It has been reported that down-staging from N2 status to N1 or N0 after ICRT in NSCLC patients correlates with better prognoses than those in patients without down-staging. 24 Our data also showed that the down-staging from T3/T4 to T1 or T2 would also correlate with good prognoses.…”
Section: Commentsupporting
confidence: 72%
“…It has been reported that down-staging from N2 status to N1 or N0 after ICRT in NSCLC patients correlates with better prognoses than those in patients without down-staging. 24 Our data also showed that the down-staging from T3/T4 to T1 or T2 would also correlate with good prognoses.…”
Section: Commentsupporting
confidence: 72%
“…Demographic information on the final study lists for both the individual patient data and aggregate data analyses is presented in Table 1 and Supplementary Table 1 . 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 …”
Section: Methodsmentioning
confidence: 99%